Nominalization in “The Subtle Art of Not Giving a Fuck” Book by Mark Manson - I Made Dennis Ary Chandra; IGB Wahyu Nugraha Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This study requires to identify the kinds of nominalizations in The Subtle Art of Not Giving a Fuck Book. Observation method applied in order collect data for this study. It used qualitative descriptive approach and theory proposed by Hamawand (2011) and Plag (2003) were applied to analyse the data. This study used both formal and informal approaches for presenting its findings and discussions. Based on the outcome, it is found that verb forming noun with 35 words (52,3 %) (-ion, -ment, -er, -ation and -or), adjective forming noun with 25 words (37,3 %) (-ness, -ce, -ity) and noun forming noun with 7 words (10,4 %) (-ship, -hood, -ist). So, even though noun forming nouns have the most suffixes, but in this study found that verb forming noun are the most.